Common Mistakes in Social Media. A Case Study on a Non-Profit Company - Tonis (Bucea-Manea), Rocsana; Gurgu, Elena (Journal of Economic Development, Environment and People, 2019)
This article is an idea about the new social media seen as a phenomenon of socializing on the Internet, specific to the last years. We believe that this phenomenon influences the daily activity of each person, carried out within the institutionalized or free time. Social media have become the channel of direct communication between companies and consumers, and that is why companies need to pay great importance to the strategic online marketing plan and allocate the funds needed for its development. We think, like most academics and researchers, that social networks have become the cheapest and most active form of customer communication and a tool for developing and deploying online businesses. Once again, it is true that technology does not help us if we forget about the main asset of the companies, the human resource. We strongly believe and sustain the idea that the success of social networks is based on the social human character or brain. By communicating, each of us looks into the mirror of the society we live in, and we expect continuous confirmation of our way of thinking, behaving, talking, etc. This is the axis on which SM is based. In this article, we are explaining in detail that the online businesses need to avoid the frequent mistakes made in commercializing through social media channels.